Trait Respect Is Linked to Reduced Gray Matter Volume in the Anterior Temporal Lobe - Nakatani, Hironori; Nonaka, Yulri; Muto, Sera; Asano, Michiko; Fujimura, Tomomi; Nakai, Tomoya; Okanoya, Kazuo (Frontiers in Human Neuroscience, 2020)
Respect is a positive other-oriented social emotion upon the recognition of excellence in others. We previously reported that respect-related brain activity in the left anterior temporal lobe (ATL). Since brain activity and structure are often involved in common cognitive functions, we investigated the morphological properties of the left ATL using voxel-based morphometry analysis. We found an association of trait respect with reduced gray matter volume (GMV) in part of the left ATL. Moreover, since the ATL is involved in general conceptual knowledge, we investigated the relationships between other social emotions with similar properties as respect and the GMV of the left ATL. We observed an association of reduced GMV with empathic concern, which is an other-oriented and affective aspect of trait empathy. Our findings indicated an association of the left ATL with other-oriented and affective aspect of social emotions.